A novel two-stage enriched air biomass gasification for producing low-tar high heating value fuel gas: Pilot verification and performance analysis. (15th April 2019) - Niu, Miaomiao; Huang, Yaji; Jin, Baosheng; Liang, Shaohua; Dong, Qing; Gu, Haiming; Sun, Rongyue
Abstract: A novel two-stage gasifier, consisting of a fluidized bed gasifier and a swirl-melting furnace, was proposed and built to gasify biomass with low ash melting temperatures into clean fuel gas. Improvements of the two-stage gasification in gas upgrading, tar removal and ash separation were confirmed by characteristic analysis of gas, tar, ash and slag. Influence of equivalence ratio (ER), oxygen distribution and gasifying agent were assessed for process optimization. Refined gas with a LHV up to 11.1 MJ/Nm 3 and a tar content lower than 1 g/Nm 3 was produced. Ash was completely vitrified with a high conversion of fixed carbon and volatile, resulting in a cold gas energy fraction of approximately 80%. Increasing ER promoted gas production but limited energy conversion efficiency and gas LHV. Proper oxygen distribution among the two stages was beneficial to decrease energy loss and increase gas quality. Increasing oxygen percentage of gasifying agent enhanced combustible gas content and improved overall gasification efficiency. Highlights: A new two-stage gasification is presented to dispose low ash melting point biomass. Tar could be effectively removed by high temperature secondary oxygen gasification. High degree carbon conversion and ash vitrification could be obtained. Improvements in biomass fuel gas quality and gasification efficiency could be confirmed. The pilot test fully verified the feasibility of two-stage gasification.